2011
DOI: 10.1080/14739879.2011.11494026
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Attitudes to Professionalism: An Opportunity for the GP Tutor?

Abstract: Sensitivity to professionalism, as defined by the GMC, was higher and exposure to unprofessional behaviour lower in first year compared to fifth year. Addressing the hidden curriculum is crucial to protect professional development; GP teachers should be aware of these findings and are ideally placed to provide mentorship and support to medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…9,10,11 Studies have shown that gender has influence on professionalism. 12,13,14 In this study, we found that the male and female clinical students' perception on professionalism were not significantly different. This finding is consistent with the report by Salam et al 10 but other study found a significantly higher score in professionalism.…”
Section: Resultmentioning
confidence: 64%
See 1 more Smart Citation
“…9,10,11 Studies have shown that gender has influence on professionalism. 12,13,14 In this study, we found that the male and female clinical students' perception on professionalism were not significantly different. This finding is consistent with the report by Salam et al 10 but other study found a significantly higher score in professionalism.…”
Section: Resultmentioning
confidence: 64%
“…This finding is consistent with the report by Salam et al 10 but other study found a significantly higher score in professionalism. 13 Items for personal development were well perceived by the clinical students who have been exposed to courses in Islamic input. The course on Akhlak and Tasawuf ensures best human interaction between doctor and patient and professional colleagues.…”
Section: Resultmentioning
confidence: 99%
“…This topic is of interest because there is a strong body of evidence that professionalism wanes as students advance in their medical training with males more negatively affected (Johnston et al, 2011). This could be due to the fact that the behaviour of mentors or senior role models (mostly male), during clinical training may be different from what they were taught to expect during pre-clinical professionalism training.…”
Section: Rationale For Choice Of Topicmentioning
confidence: 99%
“…In another study the incidence of abuse was greater than 68 percent (NagataKobayashi et al, 2006). Decline in professional development with advancing clinical training, Racism and discrimination were also problems confronting students based on findings of a recent research (Johnston et al, 2011). Although negative feedback has sometimes wrongly been interpreted as abuse by students, the evidence that this is a problem in medical training is substantial.…”
Section: Frequency Of Negative Experiences Amongst Medical Students Amentioning
confidence: 99%
“…This is similar to the idea of ah idden curriculum exerting powerful influences on the occupational socialization of medical students. Johnston et al (2011), in ac ross-sectional survey, noted aprogressive decline in the "professionalism scores" of medical students on af ive-year program of study.M ore worryingly, their anonymous free-text responses listed examples of bullying, racism, sexism, and lack of respecti nd iscriminatoryc ultures that prized "teaching by humiliation. "E xploring ethical challenges faced by traineem edics, Cordingley et al (2007) identified similar issues and suggested remedial strategies.…”
Section: Context and Culturementioning
confidence: 99%